Belle Vue Farmers’ Cooperative, St. Lucia - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2020)
Testimonial of Belle Vue Farmers’ Cooperative, St. Lucia. Climate Smart Agriculture in the Eastern Caribbean States. The Path to Sustainability and Stability of Growth in a Changing Climate